Results of Special Neck Exercises in a Patient with Cerebellar Ataxia and Axial Myoclonus Due to ADCK3 Mutation - Özlem Menevşe; Sevil Bilgin; Murat Gültekin (Türk Nöroloji Dergisi, 2021)
Cerebellar ataxia associated with the aarF-domain-containing kinase 3 (ADCK3) gene mutation is a hereditary type of ataxia related to autosomal recessive cerebellar ataxias. Additional symptoms, such as epileptic seizures, pyramidal signs, and myoclonus, may be seen in this progressive ataxia. This case report aimed to present the results of the physiotherapy and rehabilitation program of a 19-year-old patient with cerebellar ataxia and myoclonus, due to coenzyme Q10 deficiency, associated with the ADCK3 gene mutation. International cooperative ataxia rating scale, mini-mental state examination, observational posture analysis, unified myoclonus rating scale, Purdue-Pegboard test, timed up and go test, functional and computerized balance tests, and Nottingham health profile were used when evaluating the patient. The patient underwent special neck exercises consisting of reeducation of neutral posture and cervical stabilization exercises for three days a week, totaling nine weeks. At the end of the treatment, improvement in the patient’s posture, marked decrease in myoclonus, and significant improvements in fine hand skills, balance parameters, and quality of life were obtained. It is likely that the physiotherapy approach, consisting of special neck exercises, has improved postural control by contributing to the development of the sensory processes needed to achieve postural control. Therefore, special neck exercises have the potential to be an alternative treatment option for these patients.